Trends and Patterns in Digital Game-Based Learning for English Vocabulary Acquisition: A Bibliometric Analysis (2021–2025) - Fatkhur Rohman Sujarwo; Nuni Widiarti; Ellianawati Ellianawati; Fahrur Rozi (Universitas Lambung Mangkurat, 2026)
This study aims to map the trends and dynamics of research on Digital Game-Based Learning(DGBL) for vocabulary acquisition in English language learning within the EFL (English as a Foreign Language) context during the 2021–2025 period using bibliometric analysis. Rapid advancements in digital technology have driven the use of digital games to enhance engagement and effectiveness in English language learning. Previous studies indicate that DGBL improves vocabulary acquisition, motivation, and retention.In addition, most have focused on limited applications; bibliometric research on DGBL in the EFL context remains scarce. This study provides a current bibliometric analysis using various databases and visualization techniques to uncover research patterns and thematic structures. Data were collected using Publish or Perish version 8 from Crossref, Google Scholar, and Scopus, and analyzed with VOSviewer. Of 2,027 articles, 132 were selected for analysis. The results show steady growth in publications, with Crossref as the primary source. Indonesia, China, and Saudi Arabia are the main contributors. Three main clusters were identified: digital technology in education, game-based learning strategies, and vocabulary acquisition in learning English. These findings provide useful references for teachers and researchers in developing and implementing learning.